Virtual-Constraints-Based Design of Stable Oscillations of Furuta Pendulum: Theory and Experiments - Shiriaev, A.; Freidovich, L.; Robertsson, A.; Johansson, R. (Proceedings of the 45th IEEE Conference on Decision and Control, 2006)
We consider a special benchmark mechanical system with two degrees of freedom and underactuation degree one. Furuta pendulum consists of an arm, rotating in the horizontal plane, and a pendulum, attached to the end of the arm freely and moving in the vertical plane. Our goal is to create and partially shape stable oscillations of the pendulum. The approach is based on the idea of stabilization of a particular virtual holonomic constraint, imposed on the configuration coordinates. We describe here a step-by-step design procedure in details. Our approach is illustrated through successful experimental tests